2017
DOI: 10.1002/cptx.17
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Manipulation of the Stress Response Protein Metallothionein

Abstract: Metallothioneins (MTs) are small molecular weight stress response proteins that play a central role as reservoir of essential divalent heavy metal cations such as zinc and copper, and also can diminish the effects of toxic heavy metals such as mercury and cadmium. Historically, MT has been considered to be an intracellular protein with roles to play in the management of heavy metals, as a regulator of cellular redox potential, and as a buffer of free radicals. Our recent studies have highlighted immunomodulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…The protective effect of Zn on Cd-induced injury has been studied in vitro and in vivo [ 14 , 15 ], however, the underlying mechanisms remain undefined. Since Zn is a potent MT inducer via the metal-response element-binding transcription factor 1 (MTF1, [ 16 19 ]), it is possible that Zn-induced MT overexpression plays an important role in protection against Cd toxicity [ 20 24 ]. In contrast to Zn-mediated MT induction, Cd also results in MT induction as part of the cellular response to injury.…”
Section: Introductionmentioning
confidence: 99%
“…The protective effect of Zn on Cd-induced injury has been studied in vitro and in vivo [ 14 , 15 ], however, the underlying mechanisms remain undefined. Since Zn is a potent MT inducer via the metal-response element-binding transcription factor 1 (MTF1, [ 16 19 ]), it is possible that Zn-induced MT overexpression plays an important role in protection against Cd toxicity [ 20 24 ]. In contrast to Zn-mediated MT induction, Cd also results in MT induction as part of the cellular response to injury.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the LNG-IUS, COCs did not cause changes in inflammatory pathways, however both the LNG-IUS and COCs caused significant downregulation of several members of the metallothionein (MT) gene family. MT has well-documented roles in binding of heavy metals including copper for homeostasis and detoxification, and is increasingly being recognized for its role in immunomodulation, apoptosis and the stress response 26,27 . Exposure to LNG-IUS in women with endometrial hyperplasia resulted in decreased immunohistochemical detection of MT protein 28 , consistent with our results showing down-regulation of MT RNA in endometrium in both LNG-exposed groups.…”
Section: Discussionmentioning
confidence: 99%
“…Of the tested genes, the expression levels of mtl-1 and mtl-2, which encode metallothioneins, changed the most. Metallothionein is a protein with special physiological functions and plays a unique role in reducing the toxicity of heavy metals such as cadmium, nickel, and lead, as well as scavenging excessive free radicals, anti-aging, and tumor (Bhandari et al, 2017). Previous studies have shown that metallothionein can provide a stable redox environment and protect cells from oxidative stress by resisting the stress response of various organelles (Rios et al, 2018).…”
Section: Discussionmentioning
confidence: 99%